Impact of physical activity on oral health: A systematic review - Arnab Das; Ipseeta Menon; Gunjan Kumar; Arpita Singh; Kunal Jha (Journal of Family Medicine and Primary Care)
Physical activity and overall health are directly related. Physical inactivity has significant detrimental health effects over the course of a lifetime. World Health Organization (WHO) defines oral health as the absence of mouth and facial pain, oral diseases, and disorders that restrict a person’s ability to bite, chew, smile, talk, and maintain their mental health. Poor oral health has been linked to lower quality of life (QOL) and well-being, increased risk of several noncommunicable diseases (for example, hypertension, dementia, depression etc). This systematic review was registered in PROSPERO. Articles from three electronic databases PubMed, Scopus, and DOAJ, using Boolean operator from January 2013 until May 2023, were searched. Quality assessment of all studies was assessed using the NIH and JBI tool. 1909 articles were identified from e-databases, and after inclusion and exclusion criteria, a total of 17 studies were included in this literature. The systematic review suggests that whether or not physical activity generally influences overall oral health outcomes. The results of this systematic study show a relationship between people who exercise regularly and their oral health and oral health practices. People who are physically active have been found to have lower levels of inflammatory biological markers, which is linked to better oral health.